Survey Paper On Bandwidth Estimation For Video Streaming (International Journal of Engineering and Computer Science, 2017)
Video streaming is a household termnow-a-days and it is widely gaining a lot ofpopularity among mobile users. A wide variety ofmobile devices,such as smart phones and tablets,are equipped with multiple wireless networkinterfaces. A lot of videos are streamed over theInternet according to users preferences but thequestion is how to efficiently and cost-effectivelyimprove video streaming quality. In order tomaintain high video streaming quality whilereducing the wireless service cost,variousapproaches such as improving band with usingadaptive algorithms are devised. In it,the optimalvideo streaming process with WIFI is done usingbandwidth estimation and manipulation.Existingsystems consider the quality of service (QoS)requirements for video traffic, such as the start uplatency, playback fluency, average playback quality,playback smoothness and wireless service cost.Existing systems based on different survey’sinclude various bandwidth estimation tools such asSpruce,Pathload,PathChirp etc.These bandwidthestimation tools are based upon scenarios of probegap model and probe rate model.these tools help todetermine the available bandwidth based on thetransmission of packets between sender and receiverthe streaming quality is deduced and then the videostreaming quality is adjusted according to thatbandwidth as per user’s choice.The rate adaptation decision is made at the clientside. For each segment, the client can request theappropriate quality version based on its screenresolution, current available bandwidth, and bufferoccupancy status. We can let the client requestdifferent parts of one segment over different links.The main contributions is based upon threefolds.First, formulate the video streaming process overmultiple links as an MDP problem. To achievesmooth and high quality video streaming, we defineseveral actions and reward functions for each state,thus calculating the estimated bandwidth. Second,to propose an algorithm to perform bandwidthmanipulation, this will take several future steps intoconsideration to avoid playback interruption andachieve better smoothness and quality. Last, weimplement a realistic test bed using an Androidphone and Scalable Video Coding (SVC) encodedvideos to evaluate the performance. [3]